Il corpo malato dell’eroe: impurità e allontanamento - Zamperini, Enrica (O T I V M, 2017)
The aim of this paper is to investigate the relationship between purity/impurity and the sacred through the figure of Philoctetes. This relationship is based on the analogy between the ambiguity of the concept of sacred as prohibition and separation and the idea of impurity as something to avoid. The paper examines the role of the extraordinary and inordinate hero’s body in the relationship between the impurity and the sacred. Hero’s body often appears in the play as a diseased body. His physical integrity is threatened by his fault (hybris); the disease of hero’s body (nosos) represents an individual impurity that affects the whole polis. It leads to the hero’s expulsion from the city. The Philoctetes is meaningful to understand this relationship because hero’s wound makes him impure, and for this reason, he is abandoned on the Lemnos island. The hero’s rehabilitation is possible only through his healing, only if his dissimilarity is annulled and therefore purified.